Making Molecular Tools to Determine the Effect of Amino Acid Supply on Protein Synthesis - Yang, Yutong (International Journal of Social Sciences and Public Administration, 2024)
Background: The twenty amino acids making up proteins in animals are classified into three nutritional classes: EAAs, NEAAs and CEAAs. Proteins with extreme amino acid ratios are closely related to growth, malnourishment, cancer and other health problems. Previous studies have shown that the amino acid composition of a protein can influence the protein expression level. The hypothesis that CEAA-rich proteins tend to reduce expression, especially in cells proliferating quickly is expected to be proven, which may provide new ideas for amino acid therapy for some diseases. Lay Abstract: The twenty amino acids making up proteins in animals are classified into three nutritional classes: EAAs, NEAAs and CEAAs. Previous studies show that the amino acid composition of proteins can interact with amino acid availability to influence protein expression levels, independently of the amount of mRNA produced. By analysing the bioinformatic data of protein expression levels in human cells, protein expression was observed to be affected in the way that the more CEAAs present in a protein, the lower its expression, which was particularly evident in cells proliferating quickly. In this project, plasmid constructs were created that express artificial proteins containing almost only one amino acid nutritional class with a V5 epitope at the terminal. These were transfected into A549 cells to test the hypothesis from data analysis in real-life cells that proteins with extreme proportions of CEAAs tend to reduce expression and are most affected by proliferation compared with proteins with other proportions of amino acid class. The V5 tag is an epitope that can be detected by certain antibodies on Western blot or in cells. Through measuring the amount of certain A549 cell protein synthesis in different treatment groups, the results show that proteins with extreme proportions of CEAAs tend to reduce in expression but are not the most affected by proliferation. However, proteins of what amino acid composition ratio are most affected by proliferation and the specific mechanism behind the effect need further study.